Coupling of semiannual and annual variations in the SuperMAG SML and SMU indices. (1st September 2018) - Du, A.M.; Wang, K.T.; Luo, H.; Tsurutani, B.T.; Gjerloev, Jesper; Sun, Wei; Wang, Y.; Ou, Jiaming; Ge, Yasong
Abstract: It is found that the coupling between the solar wind and polar geomagnetic activity cause the annual and semiannual variation of auroral electrojet. The wavelet spectrum of the SuperMAG index, SML and SMU shows that both of the semiannual and annual variations are permanent features, and spectral power of the annual period of SML and SMU are stronger than that of the semiannual period. Due to coupling of the annual variation and the semiannual variation of SML, the diurnal variation of SML in summer months is not well correlated with results anticipated from the previous principle hypotheses [McIntosh, 1959; Russell and McPherron, 1973; Svalgaard, 1977; Cliver et al., 2000; Newell et al., 2013]. The annual/semiannual variation of SML and SMU is typically coupled together and is dependent on the local time and latitudinal variations of ionospheric conductivity and the electric field. A new index, the annual-corrected SMO index (SMO*), was suggested to indicate the semiannual variation of the westward auroral electrojet (SML). The seasonal-UT distribution of SMO* has good correlation with that predicted by the equinoctial hypothesis [McIntosh, 1959; Svalgaard, 2011]. Highlights: The annual/semiannual variation of SML and SMU is typically coupled together. We quantitatively separate the semiannual and annual variations of geomagnetic index SMU/SML. We suggested a new index (SMO*) to indicate the semiannual variation of SML.